Personal Characteristics as Predictors of Employee Commitment of Academic Staff in Universities in Uganda: A Test of Social Identity Theory - Mugizi, Wilson; Bakkabulindi, Fred E. K. (SSRN, 2018)
The study sought to examine the extent to which seven personal characteristics, namely age, sex, highest level of education attained, marital status, length of service and position in the hierarchy and self-efficacy, were predictors of employment commitment. The cross sectional-correlational study involved 301 respondents from seven universities in Uganda. Data were collected using a questionnaire whose validity and reliability were tested using factor analysis and Cronbach alpha respectively. Percentages and means were used for descriptive analysis, while multiple regression with dummies was used for inferential analysis to test the hypotheses. Results showed that while age, education level, (single) marital status, length of service and self-efficacy were significant predictors of employee commitment, sex and positions in the hierarchy were not. Pertinent conclusions were made and hence the recommendations to the effect that the directorates of human resource in the respective universities, should encourage retention of long serving staff, support staff to further their education, support their families and develop staff selfefficacy to enhance their employment commitment.
Keywords: Academic staff; Employee commitment; Personal characteristics; Regression with dummies